Perancangan Webgis Kelurahan Baratajaya Kota Surabaya - Annisaa Hamidah Imaduddina; Maria Christina Endarwati; Ardiyanto Maksimillianus Gai (Retii, 2021)
The Baratajaya Urban Spatial Data Base is an online database system application that stores and processes geospatial data and information on spatial planning and thematic areas into a publication that is more informative, easy to understand and easily accessible to the wider community as well as an instrument in the process of sharing data. The webgis database embodiment process is an evolutionary process consisting of several stages or phases of development. The development of this webgis will be continuous and requires improvement so that it requires continuous efforts in updating and developing program applications based on contemporary technology. The Webgis of Kelurahan Baratajawa is a WebGIS (Web-Geographic Information System) that has the ability to perform data processing, display and analyze data. all parties and parties. The target of the planned findings is the compilation of an E-base map which is a WebGIS (Web-Geographic Information System) Baratajaya Village, Surabaya City which has the ability to perform data processing, display and analyze data.